Reconceiving Reproductive Health Systems: Caring for Trans, Nonbinary, and Gender-Expansive People During Pregnancy and Childbirth. Issue 3 (2022) - Kukura, Elizabeth
Abstract: This article examines the barriers to quality health care for transgender, nonbinary, and gender-expansive people (TGE) who become pregnant and give birth, identifying three central themes that emerge from the literature. These insights suggest that significant reform will be necessary to ensure access to safe, appropriate, gender-affirming care for childbearing TGE people. After illustrating the need for systemic changes that untether rigid gender norms from the provision of perinatal care, the article proposes that the Midwives Model of Care offers a set of values and clinical practices that are well-suited to meet the needs of many TGE patients during pregnancy and childbirth and which should be incorporated into the healthcare system more broadly.